Mapping of individual transportation traffic-related externalities in an intercity corridor - Sampaio, Carlos (2022)
There has been an increasing trend in private vehicle ownership. Despite the flexibility, convenience, and comfort-related advantages of individual transportation, it also represents some negative impacts. This paper proposes a methodology to map the individual transportation traffic-related externalities in an intercity corridor. For that purpose, PTV VISUM is used to develop a transport model. The externalities under study are CO2 and NOx emissions, noise, safety, and congestion. After the estimation of each externality, the information is displayed in a GIS database for analysis. The mapping of such externalities allows to support regional planning policy strategies since it can be applied as an analysis tool that can be used to estimate the impacts of specific scenarios, identify blackspots and provide insights regarding future traffic flow optimization. Using this methodology, it was possible to find the largest blackspot in terms of external costs per VKM (Vehicle-kilometer), road segments that are characterized by high volumes with low road capacity. The findings highlight that the peak-hour period entails 8% higher External Costs per VKM, in particular in the national road, but for the motorway, the value is similar. The total external costs per VKM are 8% higher in the national road during peak hour, while the value is 6% higher for the motorway in the off-peak hour period. Depending on the level of congestion, the weight of each externality differs. For a V/C ratio higher than 1.2, the congestion-related externality weights 80% of the total of externalities, while for a V/C ratio lower than 0.8, the crashes-related externality (80%) is the most prevalent, followed by the CO2-related externality (16%).